2006
DOI: 10.1007/s10551-006-9189-z
|View full text |Cite
|
Sign up to set email alerts
|

Cannot Manage without The ‚Significant Other’: Mining, Corporate Social Responsibility and Local Communities in Papua New Guinea

Abstract: The increasing pressure from different facets of society exerted on multinational companies (MNCs) to become more philanthropic and claim ownership of their impacts is now becoming a standard practice. Although research in corporate social responsibility (CSR) has arguably been recent (see subsequent section), the application of activities taking a voluntary form from MNCs seem to vary reflecting a plethora of factors, particularly one obvious being the backwater local communities of developing countries where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 15 publications
1
75
0
Order By: Relevance
“…To address these issues, it is suggested that the future research should cover more CSR dimensions, such as It is obvious from the review of literature that businesses especially MNCs exercise Western style CSR practices and lack local contextual understanding (Ahmad, 2006;Khan, 2006;Lund-Thomsen, 2004;SECP, 2005). Therefore, CSR issues such as cross-cultural implications of CSR and CSR in local context (Imbun, 2006;Jamali, 2006;Min Foo, 2007;Muller, 2006) might be useful to investigate. In addition, Institutional theory could be used to understand the localised aspect of CSR.…”
Section: Conclusion and Future Research Agendamentioning
confidence: 99%
“…To address these issues, it is suggested that the future research should cover more CSR dimensions, such as It is obvious from the review of literature that businesses especially MNCs exercise Western style CSR practices and lack local contextual understanding (Ahmad, 2006;Khan, 2006;Lund-Thomsen, 2004;SECP, 2005). Therefore, CSR issues such as cross-cultural implications of CSR and CSR in local context (Imbun, 2006;Jamali, 2006;Min Foo, 2007;Muller, 2006) might be useful to investigate. In addition, Institutional theory could be used to understand the localised aspect of CSR.…”
Section: Conclusion and Future Research Agendamentioning
confidence: 99%
“…Given mining's prolific environmental, social and economic impacts, Australia-based mining companies (defined as companies which are Australian Stock Exchange-listed or which hold major headquarters or operations within Australia) have been pressured by communities [22], non-government agencies and even shareholders [23] to act sustainably and to achieve and maintain a social licence to operate, perhaps sooner and to an even greater degree than other similarly sized companies in other industries. Indeed, many Australia-based mining companies were early adopters of sustainable development principles and practices, spurred on, in many cases, by media and stakeholder scrutiny of poor environmental performance [24]. Australia-based mining companies, therefore, offer a wealth of leading-edge information which can be used to understand better how sustainable development is conceived and how this affects the criteria shaping a social licence to operate.…”
Section: Open Accessmentioning
confidence: 99%
“…Economic (corporate) sustainability, particularly in a developing country context, often revolves around legitimacy of continued operations and profitability, stakeholder power, and social issue life cycles (Royal Dutch Shell, 2008;Eweje, 2006). CSR will tend to be perceived more as a public relations strategy, but also as philanthropy and altruism in developing countries (Imbun, 2007;Amaeshi et al, 2006;Eweje, 2006;Globescan 2001;Environics International, 1999) and transitional economies (Szczepanski et al, 2009;Koladkiewicz, 2009;Brady 2005). Such CSR perceptions and practice are a function of the "level of awareness or level of assimilation of the […] construct" (Amaeshi et al, 2006: 93).…”
Section: Introductionmentioning
confidence: 99%
“…Oman's economy, like that of Nigeria, South Africa, and Papua New Guinea is primarily dependent on the extractive industry (Imbun, 2007;Amaeshi et al, 2006;Eweje, 2006). The most important extractive industry player there (albeit as joint venture partner with the government) is Shell, a FTSE listed company.…”
Section: Introductionmentioning
confidence: 99%